Surface Reconstruction for Stable Monolithic All‐Inorganic Perovskite/Organic Tandem Solar Cells with over 21% Efficiency. (20th October 2021) - Chen, Weijie; Li, Dong; Chen, Xu; Chen, Haiyang; Liu, Shuo; Yang, Haidi; Li, Xinqi; Shen, Yunxiu; Ou, Xuemei; Yang, Yang (Michael); Jiang, Lin; Li, Yaowen; et al.
Abstract: The construction of monolithic two‐terminal tandem solar cells (2T TSCs) offers the possibility of pursuing high power conversion efficiency (PCE) by overcoming the single‐junction Shockley–Queisser limit in photovoltaics. However, little attention is paid to simultaneously improve the stability by utilizing the complementary properties of various photoactive layers. Here, beyond the stacked photoactive layers featuring complementary absorption, all‐inorganic perovskite (CsPbI1.8 Br1.2 ) is chosen as the photoactive layer of the front wide‐bandgap subcell for its intrinsic high thermal stability and ultraviolet (UV)‐filtering function to address the burn‐in and UV degradation of organic rear subcells. To realize their monolithic integration, the charge recombination efficiency in the interconnecting layer (ICL) between the two types of subcells is tentatively improved by surface reconstruction of all‐inorganic perovskite using trimethylammonium chloride. The repaired CsPbI1.8 Br1.2 surface enables effective suppression of nonradiative recombination and facilitates hole transport, providing efficient charge recombination in the ICL in the 2T TSC. As a result, the all‐inorganic perovskite/organic 2T TSC delivers a promising PCE of 21.04%, accompanied by an ultrahigh open‐circuit voltage ( V oc ) of 2.05 V, which is nearly equal to the superposition of the respective V oc values of the subcells. More importantly, the 2T TSC simultaneously shows outstanding operational and UV stabilities. Abstract : A surface reconstruction strategy is proposed to optimize the surface defect states and crystallization dynamics in an all‐inorganic perovskite/organic two‐terminal tandem solar cell, leading to efficient hole transport and charge recombination in the interconnecting layer. Finally, a power conversion efficiency of 21.04% and robust operational stability are obtained.